The stromatoporoid Habrostroma in the upper Silurian (uppermost Pridoli)–Lower Devonian (Lochkovian) of North America, and the paleobiogeographic significance of H. centrotum (Girty, 1895). (January 2020) - Stock, Carl W.; Burry-Stock, Judith A.
Abstract: Three species of Habrostroma dominate stromatoporoid faunas in the Lower Devonian (Lochkovian) of five areas in North America: New York, Virginia, Maine, Bathurst Island, and Ellesmere Island. In addition, they occur in what could be the upper Silurian (uppermost Pridoli) of Virginia, and possibly New York. Measurements of nine morphologies from 127 specimens of Habrostroma were subjected to an average linkage cluster analysis. Using average linkage between groups, three distinct clusters were revealed. Group assignments made from the cluster analysis were saved, and entered into a canonical discriminant analysis with the nine morphological variables. An overall Wilks' lambda was calculated, and is statistically significant at alpha <0.001. The hit rate for classifying group 1 is 98%, that for group 2 is 100%, and that for group 3 is 97.9%; the total hit rate is 100%. The morphological variables contributing most to group membership are: (1) percent cystlike microlaminae, (2) microlaminae per mm, (3) gallery height, (4) laminae per mm, and (5) laminar thickness. The statistics confirm that there are three species: H . centrotum, H . microporum, and H . consimile . Habrostroma centrotum occurs in all five areas. This is unusual because Virginia, New York, and Maine are part of the Eastern Americas Realm, and the arctic islands are part of the Old World Realm. Separation of the realms is based on a high percentage of unique genera in each. A breach in the inter-realm barrier is proposed to have existed across the Canadian Shield during the Lochkovian. The nature of the breach is determined to be a shallow-water filter, allowing the passage of a limited number of taxa.